Preliminary evaluation of dynamic glucose enhanced MRI of the human placenta during glucose tolerance test - Luo, Jie; Turk, Esra Abaci; Gagoski, Borjan; Copeland, Natalie; Zhou, Iris Y.; Young, Vanessa; Bibbo, Carolina; Robinson, Julian N.; Zera, Chloe; Barth Jr, William H.; Roberts, Drucilla J.; Sun, Phillip Zhe; et al. (Quantitative Imaging in Medicine and Surgery, 2019)
Background: To investigate dynamic glucose enhanced (DGE) chemical exchange saturation transfer (CEST) MRI as a means to non-invasively image glucose transport in the human placenta. Methods: Continuous wave (CW) CEST MRI was performed at 3.0 Tesla. The glucose contrast enhancement (GCE) was calculated based on the magnetization transfer asymmetry (MTRasym), and the DGE was calculated with the positive side of Z-spectra in reference to the first time point. The glucose CEST (GlucoCEST) was optimized using a glucose solution phantom. Glucose solution perfused ex vivo placenta tissue was used to demonstrate GlucoCEST MRI effect. The vascular density of ex vivo placental tissue was evaluated with yellow dye after MRI scans. Finally, we preliminarily demonstrated GlucoCEST MRI in five pregnant subjects who received a glucose tolerance test. For human studies, the dynamic R2* change was captured with T2*-weighted echo planar imaging (EPI). Results: The GCE effect peaks at a saturation B1 field of about 2 μT, and the GlucoCEST effect increases linearly with the glucose concentration between 4–20 mM. In ex vivo tissue, the GlucoCEST MRI was sensitive to the glucose perfusate and the placenta vascular density. Although the in vivo GCE baseline was sensitive to field inhomogeneity and motion artifacts, the temporal evolution of the GlucoCEST effect showed a consistent and positive response after oral glucose tolerance drink. Conclusions: Despite the challenges of placental motion and field inhomogeneity, our study demonstrated the feasibility of DGE placenta MRI at 3.0 Tesla.